Sumando Custom as a Coastal Ethnic Hybrid Identity in Sibolga City, North Sumatra Province - Indah Wulandari Pulungan; Nopriyasman Nopriyasman; Gusti Asnan (Green Publisher Indonesia, 2024)
This research was conducted to explain the background to the formation of the Sumando custom, the forms of the Sumando custom, and the meaning of the Sumando custom as a hybrid ethnic identity in Pesisir Sibolga. The theory used to analyze the object of this research is hybridity theory and deconstruction theory. Research on